Perfil epidemiológico de dermatofitoses em pacientes atendidos em um laboratório privado de João Pessoa-PB, entre 2015 a 2019 e avaliação antifúngica de 2-bromo-N-fenilacetamida frente a isolados clínicos do gênero Microsporum - Andrade Júnior, Francisco Patricio de (2020)
Dermatophytoses are a type of cutaneous mycotic infection caused by species of the genera Epidermophyton, Trichophyton or Microsporum. However, even in the case of common fungal infections, there are few epidemiological studies that characterize the most susceptible populations, as well as, there is a lack of research looking for new molecules with anti-Microsporum potential. The present study aimed to elucidate the epidemiological profile of dermatophytoses in patients seen in a private laboratory in João Pessoa-PB, between 2015 and 2019, and to investigate the antifungal activity of 2-bromo-N-phenylacetamide (A1Br) against clinical isolates of the genus Microsporum. This is an epidemiological, analytical, retrospective, documentary and experimental study, in which the A1Br antifungal potential, against strains of M. canis and M. gypseum, was evaluated using the Minimum Inhibitory Concentration (MIC), Fungicidal Concentration Minimum (MFC), Association using the checkerboard method, changes in micromorphology and tests with ergosterol and sorbitol. The study was approved by the Research Ethics Committee of the Health C at UFPB, as follows: 3,770,492 Between the years 2015 to 2019, 1055 suspected mycoses were analyzed, however, only 94 cases of dermatophytosis were recorded. The profile of those affected was predominantly female (58.5%), aged 18 to 59 years (38.4%), white (53.6%) and with lesions, mainly in glabrous skin ( 38.5%), feet (33.3%) and nails (12.8%). When relating the age group to the injury site, it was noticed that injuries on glabrous skin, feet and nails, were more frequent in individuals aged 18 to 59 years, while injuries to the scalp were mostly elucidated in individuals under 18 years old. When correlating the fungal species with the lesion site, it was noted that M. canis was the main agent responsible for lesions in glabrous skin, scalp and hands, while T. rubrum was predominantly observed in nails and T. mentagrophytes in feet. Regarding the experimental results, A1Br showed MIC variations between 16 to 64 µg / mL for both strains and when comparing these results to the MIC values of ketoconazole, there was no statistically significant difference (p> 0.05). The MCF of A1Br varied between 64 µg / mL to values greater than 1024 µg / mL and the molecule showed fungistatic characteristics. However, pharmacological indifference was found when associating A1Br with ketoconazole. When analyzing the effects of A1Br on morphogenesis, it was noted that the increase in the concentration of this substance caused a decrease in fungal structures (p <0.05). Regarding the mechanism of action, it was shown that it is associated with fungal ergosterol. It is concluded that the data present in this research can foster the development of indicators and public policies for the population most susceptible to dermatophytoses and that the A1Br molecule showed strong antifungal activity and potential to become a future product for the treatment of dermatophytoses, this being the first study that sought to evaluate the antifungal potential of this substance.